Analysis of Determining Factors of Green Banking Disclosure in Sharia Commercial Banks (Study on Sharia Commercial Banks in Indonesia, 2017-2020) - Feby Aulya Wardani; Tuti Anggraini; Khairina Tambunan (Jurma : Jurnal Program Mahasiswa Kreatif, 2022)
This study aims to determine the determinants of green banking disclosure at Islamic Commercial Banks in Indonesia. The independent variables used are the number of the Board of Commissioners, Company Size, and Profitability (ROA). The data used are secondary data from annual reports, GCG reports, and sustainable reports of Islamic Commercial Banks in Indonesia for 2017-2020. The research sample consisted of 14 banks and 56 samples were obtained. The analytical technique used is panel data regression analysis with a fixed effect model using the Eviews 10 analysis tool. The results of this study are that the independent variables simultaneously affect the disclosure of green banking at Islamic Commercial Banks in Indonesia in 2017-2020. Partially, the board of commissioners affects the disclosure of green banking at Islamic Commercial Banks in Indonesia in 2017-2020. Meanwhile, Company Size does not affect the disclosure of Green Banking at Islamic Commercial Banks in Indonesia in 2017-2020. In addition, the implications of this study are also used to see the importance of implementing green banking not only because of regulations but also the importance of bank support in environmental preservation.